True crime stories. Scientific methods of criminal investigation, criminology and historiography - Valier, Claire (The British journal of criminology, 1998)
How can we catch the criminal? The history of criminology has had little to say about the place of scientific methods of criminal investigation in the discipline of criminology and in the redistribution of the power to punish that took place with the withdrawal of public execution. Thinking about this omission can act as a critical and reflexive exercise: why have we made a riddle of criminalily? Perhaps it is exactly the contours of this problem that mean that we consistently fail to catch the criminal. Perhaps there was never any mystery to be solved